2018
DOI: 10.1021/jacs.8b05238
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Mechanism May Avoid High-Oxidation State Ir(V)–H Intermediate and Coordination Complex in Alkane and Arene C–H Activation by Cationic Ir(III) Phosphine

Abstract: Organometallic reaction mechanisms are assumed to be appropriately described by minimum energy pathways mapped out by density functional theory calculations. For the two-step oxidative addition/reductive elimination mechanism for C-H activation of methane and benzene by cationic Cp*(PMe)Ir(CH), we report quasiclassical direct dynamics simulations that demonstrate the Ir-H intermediate is bypassed in a significant amount of productive trajectories initiated from vibrationally averaged velocity distributions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 51 publications
0
46
1
1
Order By: Relevance
“…Transition metal mediated C–H bond activation is a very important transformation with great potential for the functionalization of hydrocarbons. Decisive mechanistic advances have been made with the investigation of electrophilic C–H bond activation at (η 5 -C 5 Me 5 )Ir(III) centers, 11 revealing, among other details, the influence of coligands, in particular their ability to act as a base to accept the generated proton. 12 Here, we targeted the synthesis of cationic (η 5 -C 5 Me 5 )Ir(III) complexes of the terphenyl phosphines 13 PMe 2 Ar Xyl 2 and PMe 2 Ar Dipp 2 (Scheme 1).…”
mentioning
confidence: 99%
“…Transition metal mediated C–H bond activation is a very important transformation with great potential for the functionalization of hydrocarbons. Decisive mechanistic advances have been made with the investigation of electrophilic C–H bond activation at (η 5 -C 5 Me 5 )Ir(III) centers, 11 revealing, among other details, the influence of coligands, in particular their ability to act as a base to accept the generated proton. 12 Here, we targeted the synthesis of cationic (η 5 -C 5 Me 5 )Ir(III) complexes of the terphenyl phosphines 13 PMe 2 Ar Xyl 2 and PMe 2 Ar Dipp 2 (Scheme 1).…”
mentioning
confidence: 99%
“…27,28,29,30,31,32,33,34,35 Recently, we discovered dynamic effects in a few stoichiometric organometallic reactions. For example, in the C-H activation between methane and [Cp*(PMe3)Ir III (CH3)] + , 36 as well as the -hydrogen transfer for [Cp*Rh III (Et)(ethylene)] + , 37 despite a fully characterized intermediate on the DFT-potential energy landscape, direct dynamics simulations revealed that the intermediate is either sometimes or always skipped due to dynamical coupling of multiple reaction steps through dynamic matching or the lack of IVR. We also discovered dynamic effects, specifically dynamical pathway branching, in the reaction between Tp(NO)(PR3)W and benzene 38 as well as Cp(PMe3)2Re and ethylene.…”
Section: Resultsmentioning
confidence: 99%
“…Mindiola课题组 [30,31] [33,34] . 此外, 他们发现 铜催化剂形成的卡宾物种也具有活化甲烷的潜力 [35] , 尽管反应的收率只有4%, 但却为发展更经济的催化体 系提供了一种新的方向.…”
Section: 在建立金属催化剂和配体的相关反应模型基础上unclassified